2020
DOI: 10.1111/jgs.16911
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing in the 2016 Medicare Fee‐for‐Service Population

Abstract: BACKGROUND AND OBJECTIVES Opioid use and misuse are prevalent and remain a national crisis. This study identified beneficiary characteristics associated with filling opioid prescriptions, variation in opioid dosing, and opioid use with average daily doses (ADDs) equal to 120 morphine milligram equivalents (MMEs) or more in the 100% Medicare fee‐for‐service (FFS) population. DESIGN, SETTING, PARTICIPANTS, AND MEASUREMENTS In a cohort of FFS beneficiaries with 12 months of Medicare Part D coverage in 2016, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Deprescribing, the reduction of medications for which the potential harms outweigh the likelihood for benefit [ 6 ], is a solution for mitigating medication-related harms, such as falls, by aligning prescribing with goals of care and prognosis. Studies have shown that numerous older adults are prescribed opioids or BZDs in the time leading up to a serious fall [ 2 , 3 , 7 9 ], making these medications an obvious priority for deprescribing. Unfortunately, a number of barriers prevent prescribers’ ability to deprescribe medications in routine clinical practice in primary care, including lack of time, insufficient safety data, and having multiple prescribers [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deprescribing, the reduction of medications for which the potential harms outweigh the likelihood for benefit [ 6 ], is a solution for mitigating medication-related harms, such as falls, by aligning prescribing with goals of care and prognosis. Studies have shown that numerous older adults are prescribed opioids or BZDs in the time leading up to a serious fall [ 2 , 3 , 7 9 ], making these medications an obvious priority for deprescribing. Unfortunately, a number of barriers prevent prescribers’ ability to deprescribe medications in routine clinical practice in primary care, including lack of time, insufficient safety data, and having multiple prescribers [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with other studies, our study showed significant differences in the use and prescribing opioids and BZDs by sex, race, and geographic location. [1][2][3][4][5][6][7][8]14,15 Disparities in prescribing, are of great importance considering that historically marginalized individuals disproportionally experience worse health outcomes and suboptimal care. 11,16,17 Considering the potential for abuse and misuse, it is also critical to recognize that such disparities may also contribute to overprescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Women are more likely to be prescribed and fill BZD prescriptions than men, and non-White patients are less likely to be prescribed and fill BZDs compared to White patients. [1][2][3][4] Men of all races and Black patients are less likely to be prescribed and fill opioids, [4][5][6] and co-prescribing of opioids and BZD is more likely among women and less likely among Black patients. 7,8 Despite concerns around the use of BZD and opioids among older adults due to the increased risk of adverse effects, research suggests that the use of these medications is increasingly prevalent in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids and BZDs are CNS-active medications that are challenging to appropriately prescribe and monitor, yet are commonly used in older adults [ 4 , 5 ]. Although these medications are frequently used in the treatment of pain, anxiety, and insomnia, they have also been shown to be associated with injurious falls in older adults, especially when used concurrently [ 3 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%